THE CONCEPT OF KAFA'AH IN MARRIAGE ACCORDING TO ISLAMIC FAMILY LAW AND ITS RELEVANCE IN THE MODERN ERA - Septiani, Rina (PT. Hafasy Dwi Nawasena, 2025)
Kafa'ah is the principle of equality in marriage widely discussed in classical Islamic jurisprudence literature, encompassing aspects of religion, lineage, economic status, profession, and honor. This concept aims to maintain the welfare and stability of the household. Although kafa'ah is not included in the pillars or requirements for valid marriage according to Islamic law, in social practice—especially in traditional Indonesian communities—the consideration of kafa'ah is still used, often as a reason for marriage rejection due to differences in social status or family background. However, rapid social change has driven a shift in the meaning of kafa'ah, especially among the younger generation and urban communities. This study uses a qualitative normative approach with a literature review method. Data were obtained from fiqh books of four schools of thought, laws and regulations such as Law Number 1 of 1974 and the Compilation of Islamic Law, as well as secondary sources in the form of scientific journals and social surveys. Data analysis techniques were carried out descriptively-analytical and contextually with a maqashid sharia approach. The results of the study indicate that although kafa'ah does not have formal legal force in national law, this concept is still alive in the community's culture. The relevance of kafa'ah in the modern era lies in the substantial values that support the goals of marriage, such as a shared vision for life, religious commitment, and morals. Therefore, kafa'ah needs to be understood as a dynamic concept that can be reinterpreted contextually to create a family that is peaceful, loving, and compassionate.